(x^4)(3x^3-2)(4x^2+5x)
=(3x^7-2x^4)(4x^2+5x)
=12x^9+15x^8-8x^6-10x^5
answer: 12x^9+15x^8-8x^6-10x^5
That isn’t a question it is a statement
I am confident that the best option is Last one in this case.
Answer is <span>C.c + 3m
</span><span>m = price of mints
c = price of candy,
</span>
cause 1 pound of candy and 3 pounds of mints cost $5.35<span>
</span>
Answer:
Andre have more money after 4 weeks and after 6 week they have same amount of money.
Step-by-step explanation:
When Andre =100 then Elena =10.
After 4 week,
Andre = 100+(5*4)=100+20=120
In this time Elena = 10+(20*4) =10+80 = 90
After more 2months Andre have more 5+5=10
Then his total balance will be 120+10=130.
Than Elena after 2 week have 20+20=40.
Then her total balance will be 90+40=130.
That's mean 4 weeks+ extra 2 weeks total 6 weeks